Development of a traffic simulation model of UP Diliman using VISSIM - Chan, Benson James U.
Traffic simulation models serve an important role in the evaluation of traffic management schemes to alleviate traffic congestion. Simulation models may also be used to assess the traffic impact caused by changes in land use development. This study aims to initiate the development of a traffic microsimulation model for the UPDiliman. The project is split into 6 phases, with this study being the pilot phase. In Phase I, the road network for the UP Diliman Campus is established. This includes the link and connector network, intersection priority rules, and signalized traffic signals. A sub-area of the campus is chosen to be simulated, assessing the travel times of vehicles along Quirino Avenue. An activity framework for the construction of the entire model is also drafted.